An Integrated Population Model for Harvest Management of Atlantic Brant. Issue 5 (1st April 2021) - Roberts, Anthony J.; Dooley, Joshua L.; Ross, Beth E.; Nichols, Theodore C.; Leafloor, James O.; Dufour, Kevin W.
ABSTRACT: Atlantic brant ( Branta bernicla hrota ) are important game birds in the Atlantic Flyway and several long‐term monitoring data sets could assist with harvest management, including a count‐based survey and demographic data. Considering their relative strengths and weaknesses, integrated analysis to these data would likely improve harvest management, but tools for integration have not yet been developed. Managers currently use an aerial count survey on the wintering grounds, the mid‐winter survey, to set harvest regulations. We developed an integrated population model (IPM) for Atlantic brant that uses multiple data sources to simultaneously estimate population abundance, survival, and productivity. The IPM abundance estimates for data from 1975–2018 were less variable than annual mid‐winter survey counts or Lincoln estimates, presumably reflecting better accounting for observer error and incorporation of demographic estimates by the IPM. Posterior estimates of adult survival were high (0.77–0.87), and harvest rates of adults and juveniles were positively correlated with more liberal hunting regulations (i.e., hunting days and the daily bag limit). Productivity was variable, with the percent of juveniles in the winter population ranging from 1% to >40%. We found no evidence for environmental relationships with productivity. Using IPM‐predicted population abundances rather than mid‐winter survey counts alone would have meant fewer annual changes to hunting regulations since 2004. Use of the IPM could improve harvest management for Atlantic brant by providing the ability to predict abundance before annual hunting regulations are set, and by providing more stable hunting regulations, with fewer annual changes. © 2021 The Wildlife Society. Abstract : We used 43 years of data to build an integrated population model for Atlantic brant to estimate demographics and improve harvest management. The results of this model describe the effect of harvest on population growth and provide a prediction of population abundance for use in setting hunting seasons for Atlantic brant.